'It all comes back to community!': A qualitative study of Aboriginal Elders promoting cultural well‐being. (10th November 2021) - Cox, Terrance; Hoang, Ha; Mond, Jonathon; Cross, Merylin
Abstract: Objective: To examine Australian Aboriginal Elders' (Elders) views on their contributions to and their potential to contribute to the well‐being of their community. Design: Participatory action research methodology was employed. Data collection methods included yarning interviews and group circle discussions. Data were thematically analysed. Setting: The project was undertaken in collaboration with Elders from a discrete Aboriginal community in rural/remote Tasmania, an island state in southern Australia. Participants: Twelve Aboriginal community Elders. Intervention: N/A. Main outcome measures: N/A. Results: Elders were promoting cultural well‐being through interconnected themes of mentoring, cultural healing and seeking balance between health services and the community's cultural foundation. Cultural values, identity, community cohesion and connections to country were further embedded in these themes. Conclusion: The study findings draw attention to the age‐old wisdom of Aboriginal Elders, who actively promote cultural well‐being as a main determinant of community health.